Collaborative Professional Development: A Catalyst for Science Education Reform in Nigeria - Usman Rufai Fakai; Aliyu Sa’adu; Muhammad Abdullahi Argungu; Abubakar Sahabi Aliyu (Formosa Journal of Science and Technology, 2024)
This study examines the impact of collaborative professional development (CPD) on science education in Nigeria using a mixed-methods research design. Combining qualitative interviews, focus groups, and classroom observations with quantitative surveys and academic performance data, the study explores CPD's influence on teaching practices and student outcomes. The results demonstrate that CPD significantly enhances teaching practices, boosts teacher confidence, and improves student engagement and performance. Teachers reported adopting more interactive, student-centered instructional methods, particularly through Professional Learning Communities (PLCs) and peer coaching. Quantitative analysis revealed a statistically significant increase in student science test scores following CPD implementation. However, challenges such as resource constraints, time limitations, and insufficient administrative support were identified as barriers to effective CPD. The study emphasizes the need for fostering a collaborative culture in schools, ensuring adequate resources, and supporting continuous professional growth through structured policies. These findings highlight the importance of integrating CPD into teacher evaluation and career progression frameworks to achieve sustainable improvements in science education. By addressing these challenges and maximizing the benefits of CPD, Nigerian schools can enhance science education quality, leading to improved student outcomes and overall educational development.